Relationship Between Demographic and Radiographic Characteristics and Second Ray Pathology in Hallux Valgus Patients. Issue 1 (23rd March 2020) - Cronin, Samantha; Conti, Matthew; Williams, Nicholas; Ellis, Scott J.
Background: Hallux valgus can alter load bearing in the foot leading to abnormal forces on the second toe. The purpose of this study was to determine demographic and radiographic factors associated with second ray hammertoes in hallux valgus using 3-dimensional weightbearing CT scans. Methods: Seventy-one patients who underwent a modified Lapidus procedure for hallux valgus with preoperative weightbearing CT scans were separated into 2 groups: (1) hallux valgus only (47 feet) and (2) hallux valgus with second ray hammertoe (29 feet). Preoperative age, body mass index (BMI), sex, hallux valgus angle (HVA), intermetatarsal angle (IMA), absolute and effective metatarsal (MT) lengths, ratios between metatarsal lengths, Meary angle, metatarsus adductus angle (MAA), and pronation were measured. Mean values of continuous variables were compared and both simple and multivariable logistic regression models were used to evaluate associations between variables and hammertoe occurrence. Results: Patients in the hammertoe group were found to be significantly older and have higher BMIs, HVAs, effective second MT lengths, IMAs, and more apex plantar Meary angles (all P < .05). The multivariable analysis demonstrated that a higher IMA and a more apex plantar Meary angle were the only significant predictors of second ray hammertoe risk ( P = .03 and P = .01, respectively) once corrected for age and BMI. Conclusion: Significant associations were found between older age, higher BMI, and more severe deformity and the occurrence of hammertoe in hallux valgus patients. These results may help clinicians counsel hallux valgus patients about the risk of developing an advanced hammertoe deformity. Level of Evidence: Level III, retrospective comparative series